Two-dimensional cobalt ferrite through direct chemical vapor deposition for efficient oxygen evolution reaction - Wu, Yao (2024)
Two-dimensional (2D) transition metal oxides (TMOs) are promising electrocatalysts for the new energy industry, owing to their earth-abundancy, excellent performance, and unique physicochemical properties. However, microscopic electrochemical study for 2D TMOs is still lacking to provide detailed electrocatalytic mechanisms due to the challenges in synthesizing 2D TMOs with high quality and controlled thickness, which is indispensable for the microscopic studies. In this study, we report the direct synthesis of 2D cobalt ferrite (CoFeO) using a chemical vapor deposition (CVD) method. The as-synthesized 2D CoFeO possesses a well-crystallized spinel structure with an ultrathin thickness of 6.8 nm. Its oxygen evolution reaction (OER) properties under alkaline conditions were accurately assessed using an ultra-microelectrode testing platform. The (111) facet of the 2D CoFeO exhibits a low overpotential of 330 mV at a current density of 10 mA cm–2 and a high current density of ~142 mA cm–2 at an overpotential of 570 mV. The OER mechanism of the 2D CoFeO was analyzed using density functional theory (DFT) calculations, which reveal the bimetallic sites on the surface reduce the energy barrier and facilitate the reaction. Moreover, we demonstrate the reduced thickness of 2D CoFeO improves the OER activity by lowering the bulk resistance and improving the utilization of active sites, which was confirmed by the thickness-activity dependency (6.8 to 35 nm) tests using the ultra-microelectrode platform. Furthermore, the practical values of the as-prepared 2D CoFeO was demonstrated by synthesizing a large-area continuous film and collecting high OER activity and superb durability from macro-electrochemical experiments. Our study provides new solutions for the controlled synthesis of 2D TMOs electrocatalysts and uncovers the electrocatalytic mechanisms with the ultra-microelectrode platform, which provides new insights for exploring the inherent properties and applications of 2D materials in electrocatalysis.